Flight-to-Quality or Flight-to-Liquidity? Evidence from the Euro-Area Bond Market - Beber, Alessandro; Brandt, Michael W.; Kavajecz, Kenneth A. (Review of Financial Studies, 2009)
Do bond investors demand credit quality or liquidity? The answer is both, but at different times and for different reasons. Using data on the Euro-area government bond market, which features a unique negative correlation between credit quality and liquidity across countries, we show that the bulk of sovereign yield spreads is explained by differences in credit quality, though liquidity plays a nontrivial role, especially for low credit risk countries and during times of heightened market uncertainty. In contrast, the destination of large flows into the bond market is determined almost exclusively by liquidity.We conclude that credit quality matters for bond valuation but that, in times of market stress, investors chase liquidity, not credit quality. (JEL G10, G12)